Synthesis of pumice-TiO2 nanoflakes for sonocatalytic degradation of famotidine. (20th November 2018) - Rad, Tannaz Sadeghi; Khataee, Alireza; Kayan, Berkant; Kalderis, Dimitrios; Akay, Sema
Abstract: Pumice-TiO2 was synthesized through simple sol-gel method. The successful synthesis of the catalyst was verified by SEM, EDS, XRF, FT-IR and BET techniques. Then, a sonocatalytic process was performed to degrade famotidine in the presence of the synthesized catalyst and under ultrasonic irradiation. The removal efficiency of the sonocatalytic process with pumice‒TiO2, TiO2, pumice and sonolysis within 70 min was 71.1%, 33.9%, 31.1% and 8.9%, respectively. The main operational parameters which were examined in this study were catalyst dosage, pH, famotidine concentration and ultrasonic power which were optimized as 1.5 g/L, 5, 20 mg/L and 150 W, respectively. Moreover, the addition of radical scavengers (EDTA, Na2 SO4 and 1, 4–benzoquinone) and enhancers (H2 O2 and K2 S2 O8 ) which can affect the removal efficiency were investigated. Diverse degradation by-products were identified using GC‒MS analysis. Eventually, the reusability tests confirmed that the synthesized pumice‒TiO2 catalyst had significant stability after 5 consecutive runs. Graphical abstract: Synthesis and characterization of pumice-TiO2 and its application in the heterogeneous sonocatalytic process. Image 1 Highlights: Synthesis of pumice‒TiO2 by modified sol-gel method. Application of pumice‒TiO2 nanoflakes in sonocatalytic degradation of FMT. Examining the effects of radical scavengers and reaction enhancers on RE% of FMT. Identifying sixteen FMT degradation intermediates by GC‒MS.